Diffuse Strong Membrane Expression of MIC2 (CD99) in Anaplastic Large Cell Lymphoma: A Diagnostic Challenge - Renu Sukumaran; Jayasudha A Vasudevan; Jayasree Kattoor; Sugeeth M Thambi; Jiju George Zachariah (Journal of Clinical and Diagnostic Research, 2021)
The MIC2 [Cluster of Differentiation 99 (CD99)] has been widely used in making the diagnosis of Ewing’s sarcoma and diffuse strong membrane expression is the characteristic finding. The CD99 is a sensitive marker of Ewing’s sarcoma, but not specific. Studies have shown expression of CD99 in a wide variety of neoplasms which include epithelial, mesenchymal and haematopoietic neoplasms. In these tumours, the positivity of CD99 is described as variable with focal/patchy, irregular, membrane/cytoplasmic staining. Among the haematopoetic neoplasms, diffuse strong positivity of CD99 is seen in blasts which include T-lymphoblasts, B-lymphoblasts and myeloblasts. Recent studies have demonstrated positive staining of CD99 in mature lymphomas where the pattern of expression is heterogenous and highly variable. Herein, authors report the case of a 42-year-old male patient with expansile destructive lesion in right scapula with large soft tissue component. With clinical diagnosis of sarcoma, biopsy was taken which showed large atypical cells arranged diffusely, focally around vessels and in vague rosettoid pattern. In the initial immunopanel, neoplastic cells showed diffuse strong membrane expression of CD99 and were negative for cytokeratin, synaptophysin, chromogranin, desmin and S100. On further examination, the neoplastic cells showed focal weak to moderate positivity for CD45, diffuse strong positivity for CD30 and strong positivity for Anaplastic Lymphoma Kinase (ALK). Diagnosis of ALK positive Anaplastic Large Cell Lymphoma (ALCL) was given. The awareness of diffuse strong membrane pattern of staining of CD99 in ALCL will help to avoid misdiagnosis especially in cases with atypical clinical presentations.